Researching tourism, leisure and hospitality for your dissertation - Mason, Peter (2014)
It provides a discussion of quantitative, qualitative and mixed methods approaches, looking at key differences and similarities. A must-have text for all students on how best to conduct research, compile your findings and to present them in the resulting dissertation.